CONTRIBUTIONS OF IBN AL-KAFANI IN MEDICINE - Dr. Warood Nouri Hussein Al-Moussawi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This topic deals with the scientific aspect of one of the Mamluk figures, this is Muhammad Ibn Ibrahim, known as Ibn Al-Akfani (died: 749 AH / 1248 AD), who contributed to the development of medical science. Because of his medical experience and practice, he was also an encyclopedic who experienced more than one science. He is a doctor and researcher, a scientist of wisdom, a mathematician, these sciences are the closest to mankind and have a weight among the sciences of Muslims. This scientist lived in a period of stagnation on the earth’s sciences in general and medicine, especially after the Arab and Muslim scholars illuminated the dark period, which was clouded by the Mongols (656 AH / 1258 AD), the heritage of Arabs in this science moved to Europe.